2012
DOI: 10.1111/j.1744-9987.2012.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Calcification is an Independent Predictor of Cardiovascular Events in Peritoneal Dialysis Patients

Abstract: Abdominal aortic calcification (AAC) is reported as a predictor for cardiovascular events in general population and in hemodialysis patients. At present, there are no AAC data in peritoneal dialysis. The purpose of this study was to evaluate the prognostic role of AAC score on cardiovascular events in peritoneal dialysis patients. Seventy‐four peritoneal dialysis patients were enrolled. AAC was measured on baseline lateral abdomen radiographs by the semi‐quantitative method as described by Kauppila. The other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
1
33
1
1
Order By: Relevance
“…AAC is a common finding on imaging studies, especially with advancing age, and it is associated with cardiovascular and renal diseases [9][10][11]. Due to the increasing number of older kidney donors, incidental AAC is noted with increasing frequency in otherwise healthy donors during their predonation imaging workup.…”
Section: Discussionmentioning
confidence: 99%
“…AAC is a common finding on imaging studies, especially with advancing age, and it is associated with cardiovascular and renal diseases [9][10][11]. Due to the increasing number of older kidney donors, incidental AAC is noted with increasing frequency in otherwise healthy donors during their predonation imaging workup.…”
Section: Discussionmentioning
confidence: 99%
“…There was only one study previously that used AAC score in prediction of cardiovascular events in PD patients . Francesca Martino et al reported AAC that can be an independent predictor for cardiovascular events in a study of 74 PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, cardiovascular events were defined as non‐fatal myocardial infarction, prolonged angina pectoris, limb ischaemia, transient ischaemia attack, and cardiovascular death. In our study, we aimed to know the association between AAC and CAD . We defined CAD events as myocardial ischaemia symptoms with positive finding in coronary angiography study.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial media calcification has previously been shown to be an independent risk factor for mortality in HD patients [14]. Martino et al [15] showed for the first time the predictive value of abdominal AoACs for outcomes in Italian PD patients. In a recent report from Korea [16], 184 dialysis patients (32% PD) were enrolled.…”
Section: Discussionmentioning
confidence: 99%